Effect of heavy metal contamination on soil nematode communities in urban brownfields - Zhongqi Huo; Zhiwei Li; Pingting Guan; Fengxue Shi; Haibo Jiang; Chunguang He; Zhongqiang Wang (Global Ecology and Conservation, 2024)
Heavy metal contamination in urban brownfields can pose serious threats to the soil ecosystem. Soil nematode communities can respond rapidly to minor alterations in the soil environment over brief time intervals and are extensively employed to track changes in the soil environment. Here, we investigated the impact of heavy metal contamination on soil nematode communities and assessed the ecological risks associated with brownfields. We analyzed heavy metal contamination and soil nematode community structure in a representative urban brownfield and its neighboring urban park. The results showed that the brownfield was predominantly impacted by chromium (Cr) contamination. Plant parasites served as the primary source for soil nematodes in the park, whereas bacterivores fulfilled this role in the brownfield. Omnivores-predators decrease or even disappear with the intensification of heavy metal contamination. Acrobeloides exhibited tolerance to heavy metal contamination. Based on life history strategy, nematode communities could be classified into five colonizer-persister (c-p) groups, and the c-p values were ranked from 1 (short generation time and high colonization ability and fecundity) to 5 (long generation time and low colonization ability and fecundity). Soil nematode communities with c-p values ranging from 1 to 3 exhibited a significant negative correlation with hexavalent chromium [Cr (VI)], while those with c-p values of 4 and 5 (representing high trophic level communities) showed a significant positive correlation. We postulate that bacterivores exhibit superior adaptations to heavy metal contamination. Specific nematode taxa can indicate the pollution status of elements. Soil nematode communities at high trophic levels are powerful indicators of response to Cr (VI) contamination.